Crown O’Maine Organic Cooperative - Cook, Leah (Maine Policy Review, 2011)
The article describes how Crown O’Maine Organic Cooperative has grown from a small venture marketing one Aroostook County family farm’s potatoes to a statewide distribution company for organic foods
Keywords: Maine; organic foods cooperative